A compact wideband dual‐polarized linear array with hybrid structure and resistive loadings. Issue 7 (25th March 2019) - Zhang, Hangyu; Yang, Shiwen; Xiao, Shiwei; Huang, Ming; Zhou, Li; Chen, Yikai; Qu, Shiwei
Abstract: A wideband, wide‐scan dual‐polarized linear tightly coupled dipole array is presented. The array is based on a prior work, but it employs a hybrid design of planar cross‐finger dipoles and vertical tapered dipoles to form a non‐oversampled aperture with reduced array width and robust structure. Moreover, wider bandwidth and lower profile height are also achieved in the array as compared to the prior work by introducing resistive loadings between dipoles and ground plane, at the expense of acceptable gain loss. Consequently, the array with width of 99.8 mm and profile height of 86.3 mm provides a performance of 5.7:1 bandwidth (0.35‐2 GHz) for active Voltage Standing Wave Ratio (VSWR) < 3.0 while scanning up to 50°, with orthogonal port isolation below −15 dB. A 1 × 18 prototype array was fabricated and measured, showing good agreement with simulations.